SYSTEMATIC LITERATURE REVIEW: PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF - Fahri Saputra; Hawa Liberna (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Problem Based Learning is a teaching approach that emphasizes the role of students by connecting mathematical concepts to issues in everyday life to encourage the learning process. The purpose of this study was to evaluate the effect of the problem based learning (PBL) learning model on creative thinking skills using a systematic literature review method. By collecting and reviewing research results from various scientific journals, this article evaluates how effective PBL is in improving creative thinking skills in various educational settings. Based on the results of the review, the Problem Based Learning Model has been shown to have a significant impact on students' thinking skills through teaching that is oriented to problems that are often encountered in everyday life. This article can be used as a reference for teachers to integrate PBL into the curriculum to improve student creativity.